Bibliometric analysis of literature regarding ostomy research based on the Web of Science database - Gao Lan; Cao Xiu-Zhen; Zhang Ying; Liu Tai-Fang; Zhang Ai-Hua (Sciendo, 2018)
To analyze the literature status and research hotspots of Science Citation Index (SCI)-related ostomy in the world and to provide references for scientific research and clinical work in the stoma care field.